2020
DOI: 10.1002/jmv.26343
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe hand, foot, and mouth disease infected with Coxsackievirus A6: A hospital‐based case‐control study

Abstract: Coxsackievirus 6 (CV‐A6) has been emerging as another predominant serotype for severe hand, foot, and mouth disease (HFMD) in China, after the introduction of enterovirus 71 inactivated vaccine (EV71 vaccine) for 3 years. Data on the risk factors for severe HFMD infected with CV‐A6 are limited. We interviewed the caregivers to collected data on HFMD patients who sought medical care in the People's Hospital of Baoan district, Shenzhen, from 2015 to 2017. Totally, 131 severe patients were frequency‐matched by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is worth noting that out of the annual reported HFMD cases in mainland China since 2013, the proportion caused by coxsackievirus A6 (CVA6) has increased every year, and at present, has surpassed enterovirus 71 (EV-A71) and coxsackievirus A16 (CVA16), the leading pathogens in many provinces of China [ 2 , 3 ]. CVA6-related HFMD presents several clinical features, such as atypical herpes and nail removal, which are sometimes complicated by severe clinical symptoms such as meningitis and encephalitis [ 4 , 5 , 6 , 7 ]. However, no vaccine or effective drugs are present [ 8 ], and the pathogenesis of CVA6-associated diseases such as HFMD, meningitis, and encephalitis is unclear [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that out of the annual reported HFMD cases in mainland China since 2013, the proportion caused by coxsackievirus A6 (CVA6) has increased every year, and at present, has surpassed enterovirus 71 (EV-A71) and coxsackievirus A16 (CVA16), the leading pathogens in many provinces of China [ 2 , 3 ]. CVA6-related HFMD presents several clinical features, such as atypical herpes and nail removal, which are sometimes complicated by severe clinical symptoms such as meningitis and encephalitis [ 4 , 5 , 6 , 7 ]. However, no vaccine or effective drugs are present [ 8 ], and the pathogenesis of CVA6-associated diseases such as HFMD, meningitis, and encephalitis is unclear [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming majority of prior studies mainly focused on examining the associations between severe HFMD and individual-level risk factors, such as individual demographic characteristics, early clinical manifestations, and genetic susceptibility. It has been found that younger [13] and male sex [14] were more vulnerable to severe HFMD, while breastfeeding and hand washing after playing [15] were found to be protective. Clinical manifestations including high fever, vomiting, myoclonic twitching, and elevated serum interleukins and interferon-γ levels were found to be early indicators of severe cases [16].…”
Section: Introductionmentioning
confidence: 99%